VAT Divergence in India: An Analytical Study of its Impact in Punjab - Bagga, Tejwant Singh; Arora, Prof. Sunil K. (Indian Journal of Finance, 2011)
This paper evaluates the effect of VAT regime which was implemented in India to bring uniformity and balanced economic development. VAT divergence still existing intra-state and inter-state. The study highlights the terror of VAT inconsistency having varied product rates resulting in industrial migration from high VAT states to low VAT states/non-VAT states.